1999
DOI: 10.1097/00005344-199911000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Properties of Pyruvate and Protection of the Ischemic Rat Heart During Cardioplegia

Abstract: Formation of oxygen free radicals during heart transplantation seems to be related to the alterations occurring during ischemia and reperfusion and could explain the short preservation time of donor hearts. The aim of our study was (a) to analyze the protective effects of pyruvate during cold cardioplegia and ischemia/reperfusion sequence, and (b) to investigate in vitro the radical scavenging properties of this compound. After 30 min of perfusion, isolated working rat hearts were arrested by cardioplegic solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…Previously observed anti-apoptotic effects of ROS scavengers (Lieberthal et al, 1998;Pong et al, 2001) are consistent with the preserved Na + , K + -pump function observed in this study. Pyruvate is well-known for its direct antioxidant effect of reacting with H2O2 to form water and carbon dioxide (Crestanello et al, 1998;Varma et al, 1998); it may also possess a hydroxyl radical scavenging property (Dobsak et al, 1999) or stimulate NADPH-dependent peroxide scavenging systems (Cavallini et al, 1990). In our study both exogenous H2O2 and endogenous ROS induced by menadione, DMNQ, or apoptotic insults inhibited Ipump.…”
Section: Discussionsupporting
confidence: 46%
“…Previously observed anti-apoptotic effects of ROS scavengers (Lieberthal et al, 1998;Pong et al, 2001) are consistent with the preserved Na + , K + -pump function observed in this study. Pyruvate is well-known for its direct antioxidant effect of reacting with H2O2 to form water and carbon dioxide (Crestanello et al, 1998;Varma et al, 1998); it may also possess a hydroxyl radical scavenging property (Dobsak et al, 1999) or stimulate NADPH-dependent peroxide scavenging systems (Cavallini et al, 1990). In our study both exogenous H2O2 and endogenous ROS induced by menadione, DMNQ, or apoptotic insults inhibited Ipump.…”
Section: Discussionsupporting
confidence: 46%
“…It is well known that pyruvate is an ROS scavenger (Adickes and Andresen, 1943;Bunton, 1949;Melzer and Schmidt, 1988;Dobsak et al, 1999), and data are available suggesting that EP is as well (Varma et al, 1998;Tawadrous et al, 2002). NAC, a derivative of the amino acid L-cysteine, is both an ROS scavenger itself (Aruoma et al, 1989) and a precursor for the synthesis of the important endogenous antioxidant, GSH (Fernandez et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is suggested by the close chemical similarity between EP and pyruvate, a compound that is known to be an effective scavenger of reactive oxygen species (ROS) (Adickes and Andresen, 1943;Bunton, 1949;Melzer and Schmidt, 1988;Dobsak et al, 1999). An oxidizing environment, particularly in the cytosol, has been implicated in the activation of proinflammatory signaling molecules, such as NF-B (Schreck et al, 1992;Oka et al, 2000;Schoonbroodt et al, 2000;Livolsi et al, 2001;Rahman et al, 2001) and p38 mitogen-activated protein kinase .…”
mentioning
confidence: 99%
“…The concentrations used in the study were based on previous works. 7,10,13,15) Ascorbic acid was used as a reference antioxidant in all the experiments. A stock solution of NaOCl was prepared in water, and its concentration was determined spectrophotometrically at 290 nm, using a molar extinction coefficient of 350 M À1 cm À1 .…”
Section: Methodsmentioning
confidence: 99%
“…5) It reduces hydrogen peroxide to water 6) and scavenges the hydroxyl radical 7) by non-enzymatic decarboxylation.…”
mentioning
confidence: 99%